THE SCIENTIFIC RESEARCH METHODS OF PEDAGOGICAL SCIENCE (The Role of Exact Sciences in the Era of Modern Development, 2024)
In this article, the scientific research methods of pedagogical science and the requirements for scientific research methods are widely covered and there are questions about what and how to teach these methods in life and in the theory of knowledge of the objective world, and who should be educated. We will cover them in detail below.